Tourism Management by Lecturers as a Function of Management Roles To Achieve Sustainable Tourism - Andi Kurniawati; R. Rachmiyantono W.H.; Mis Widya Andelina (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2023)
Tourism provides many economic benefits from its development, and there is no doubt that Indonesia has advantages in the form of high potential in terms of tourism resources. Several obstacles that arise in the process of developing Sustainable Tourism include: First, regarding the use of existing resources based on sustainable principles. Second, the concept of sustainable tourism development can be applied and run parallel to other ongoing development processes. Third, regarding ways to change the perceptions, attitudes and motivations of stakeholders in accordance with new directions and criteria for tourism development. The relationship between Management Functions, Lecturer Functions, and Sustainable Tourism explains that the 5 Management functions (Planning); Organizing; Motivating/Directing; Supervising; Controlling; Assessment/Evaluating) are the basis for implementation The function of a lecturer is also the task of the Tri Dharma of Higher Education (Research and Community Service) which can run systematically and continuously with the aim of realizing Sustainable Tourism through Government Policy and support from the community and various related elements.